Listing Decisions Under the Endangered Species Act: Why Better Science Isn't Always Better Policy - Holly Doremus (Washington University Law Quarterly, 1997)
This Article offers an alternative approach to ESA listing determinations which would better combine scientific credibility with democratic legitimacy. As background to the current problem, Part II explains the origins of the ESA's stringent strictly science mandate. Part III considers the nature and limits of scientific information and explains how the scientific process can identify the best available scientific information. Part IV evaluates the specific decisions required for ESA listings in light of the strictly science mandate, explaining why these decisions require input from beyond the realm of scientific information. Part IV goes on to demonstrate that the incompatibility of the strictly science mandate with reality has led to inconsistent and incoherent policy choices. Finally, Part V suggests improvements to the listing process. Congress should acknowledge the subjective elements of listing determinations and open those parts of the decision to a more democratic process. The agencies may, indeed must, continue to rely on highly uncertain scientific data in making listing decisions, but should do so through a process which facilitates broad public review. These changes would allow the agencies to bring the best scientific knowledge to bear on the problem of species extinction without overriding the legitimate public role in non-scientific policy choices.
Keywords: Endangered species; Evidence; Expert